2018
DOI: 10.1515/ohs-2018-0023
|View full text |Cite
|
Sign up to set email alerts
|

Some morphometric features of congeneric pipefish species (Syngnathus abaster Risso 1826, Syngnathus acus Linnaeus, 1758) distributed in Lake Bafa (Turkey)

Abstract: The study was carried out between November 2014 and March 2016 to determine certain morphometric characteristics of two pipefish species occurring in Lake Bafa, Syngnathus abaster and Syngnathus acus. A total of 211 pipefish were captured during the sampling, including 77 individuals of S. abaster (♀: 25; ♂: 44; immature: 8) and 134 individuals of S. acus (♀: 31; ♂: 76; immature: 27). The male-female ratios were 1:1.76 and 1:2.45, respectively. A difference was found in sex ratios between the two species (p &l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 29 publications
1
7
1
Order By: Relevance
“…The weight-length relationships in immature fishes (b = 3.32-3.35) agreed with the positive allometric growth reported in southern Portugal (b = 3.33-3.34) [6,76], being above and below those reported for South Africa (b = 3.07) [74] and the Aegean Sea (b = 3.71-3.73) [5,8,77], respectively. Differences in length-weight parameters across the regions might be due to dissimilarities in biotic and abiotic factors [6].…”
Section: Population Characteristicssupporting
confidence: 82%
See 2 more Smart Citations
“…The weight-length relationships in immature fishes (b = 3.32-3.35) agreed with the positive allometric growth reported in southern Portugal (b = 3.33-3.34) [6,76], being above and below those reported for South Africa (b = 3.07) [74] and the Aegean Sea (b = 3.71-3.73) [5,8,77], respectively. Differences in length-weight parameters across the regions might be due to dissimilarities in biotic and abiotic factors [6].…”
Section: Population Characteristicssupporting
confidence: 82%
“…However, the large size in Cíes individuals agreed with those in eelgrass meadows populations from the northern Atlantic [4,6,75]. Hence, the length in S. acus adults seems to rely on its geographical origin [8]. Additionally, the adult size also seemed to determine the egg/larval size, as suggested by comparing the population from Cíes with those from the Aegean Sea [2] or from Ria de Aveiro in Portugal [13], whose eggs, larvae, and adults were notably smaller.…”
Section: Population Characteristicsmentioning
confidence: 54%
See 1 more Smart Citation
“…According to these comparisons, b value of S. abaster in this study is found to be higher than b values obtained from other studies (Gurkan and Innal, 2018;Cakić et al, 2002;Khrystenko et al, 2015;Taylan et al, 2018) and similarly b value S.acus is lower than those given by Gurkan Taşkavak (2007) and Yildiz (2015).…”
Section: Resultscontrasting
confidence: 63%
“…However, the large size in Cíes individuals agreed with those in eelgrass meadows populations from the northern Atlantic [4,6,75]. Hence, the length in S. acus adults seems to rely on its geographical origin [8]. Additionally, adult size also seemed to determine egg/larval size as suggested by comparing the population from Cíes with those from the Aegean Sea [2] or Ria de Aveiro in Portugal [13], whose eggs, larvae and adults were notably smaller.…”
Section: Population Characteristicsmentioning
confidence: 68%